RELEVANSI PANCASILA SEBAGAI DASAR IDEOLOGI DAN MORAL BANGSA INDONESIA - Zainudin Hasan; Fahri Reifal Setiawan; Subhan Syahrezal; M. Ihsan Putra Devary; A, Fakhry Yoga Satya; M. Maliqi Berlando (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Pancasila as a state ideology plays an important role in shaping the nation's morals. This article aims to analyze how the development of the Pancasila ideology can contribute to building morals. The research method used is empirical normative with data collection through literature studies, semi-structured interviews. The results of the study indicate that internalization of Pancasila values through formal education, campus programs, and community service programs can strengthen the attitude of love, tolerance, and national morals. The results of the study indicate that Pancasila values remain relevant.